2005
DOI: 10.1080/00015550410025444
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Acids do not Enhance Sodium Lauryl Sulphate-induced Cumulative Irritant Contact Dermatitis In vivo

Abstract: Combined exposure to different irritants in the workplace may lead to irritant contact dermatitis, which is the main type of occupational dermatitis among bakers and confectioners. Following previous work on "tandem irritation", a panel of healthy volunteers was exposed twice daily for 4 days to the organic fruit acids: citric, malic, and lactic acid, either alone or in tandem application with 0.5% sodium lauryl sulphate (SLS) in a repetitive irritation test. Irritant cutaneous reactions were quantified by vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 21 publications
1
30
0
2
Order By: Relevance
“…in fish and fish products, cheese, meat and fermented foods [2]. We could demonstrate that sequential ('tandem') application by using the 'tandem repeated irritation test' [14][15][16][17] of different irritants modifies the cutaneous response in contrast to repeated exposure to the specific irritant alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in fish and fish products, cheese, meat and fermented foods [2]. We could demonstrate that sequential ('tandem') application by using the 'tandem repeated irritation test' [14][15][16][17] of different irritants modifies the cutaneous response in contrast to repeated exposure to the specific irritant alone.…”
Section: Discussionmentioning
confidence: 99%
“…Irritant contact dermatitis studies usually focused on different effects of single irritant exposures [3][4][5][6], in particular sodium lauryl sulphate (SLS) [6][7][8][9][10][11][12][13]. Recently, we have been able to demonstrate that sequential ('tandem') application of different irritants may modify the cutaneous response indicating an aggravating effect of the combination of irritants [14][15][16][17]. It has been shown that the stratum corneum (SC) pH is important for barrier-related parameters, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are examples of tandem irritation studies, where no additive irritant potential of specific combined exposures was confirmed. N-propanol, a common alcoholic ingredient of skin disinfectants, did not enhance cumulative skin irritation when used with SLS [16], and the same was demonstrated for fruit acids [28]. …”
Section: Discussionmentioning
confidence: 99%
“…The TRIT has since been used to study tandem sequential exposures with SLS and a variety of other chemicals such as propanol and a variety of fruit acids such as citric, malic, and lactic acid [61,62]. A thorough review of tandem irritation studies to date was done by Kartona and Maibach.…”
Section: Methodsmentioning
confidence: 99%